A theory of intervention model to define the essential characteristics of music to support emotion regulation development in early childhood - Sena Moore, Kimberly; Burbach, Kailah; Hanson-Abromeit, Deanna (Frontiers in Neuroscience, 2025)
Recent work in the area of health intervention development has emphasized the need to articulate a theory of intervention. This begins with the development of a working theoretical model, which includes three elements: (1) theory of the health problem, (2) theory of change, and (3) theory of implementation. The purpose of this project was to expand and refine the intervention theory underlying the music-based intervention, Musical Contour Regulation Facilitation (MCRF). MCRF is a multi-component music intervention designed to promote emotion regulation (ER) development in early childhood. Preschooler ER is characterized by greater self-regulation of emotions, increased understanding and use of socially– and culturally–appropriate emotion display rules, and decreased reliance on caregivers for ER needs. Further, it is informed by determinants, factors such as temperament and attachment style, that serve as a protective or risk function for the development of adaptive ER skills. We propose that the determinants associated with ER development that can be modified by a music intervention include physiological arousal (i.e., parasympathetic reactivity as measured by vagal tone), cognitive skills (specifically effortful control), and coregulation (both peer-peer and adult-peer). This can occur through both bottom-up and top-down neural mechanisms, specifically music’s influence on physiologic arousal and attentional processes. As such, this intervention theory informs the design and delivery of the MCRF intervention components, including the specific and non-specific components of the intervention. The specific components define the active ingredients needed to produce the intended outcomes for preschooler ER development through the Therapeutic Function of Music (TFM) Plan, with an emphasis on the role of tempo in the intervention. Non-specific intervention components include the specific types of music experiences and interventionist facilitation techniques.